Victimization study of cybercrime related fraud and scams in the city of Mar del Plata, Argentina. (LACCEI, 2024)
The digital transformation of organizations, accelerated by the COVID 19 pandemic, forced millions of people to use different technological tools to continue carrying out their daily activities, such as making purchases, banking procedures or maintaining social interactions. This situation generated an increase in cybercrime, specifically cyber scams and cyber fraud, however, in Argentina there are no official statistics in this regard. This paper presents a victimization study carried out during the year 2021 in the city of Mar del Plata, Argentina in order to investigate and collect information on the commission of crimes mediated by technology, in order to contribute to the design of crime policies. public safety, as a first situational diagnosis.